Cold sintering of bioglass and bioglass/polymer composites - Andrews, Jessica (2023)
Bioactive glasses are widely utilized to regenerate bone tissue and aid bonding of orthopedic implants. Forming composites of bioglass with bioactive polymers allow the mechanical properties and biological response to be tailored. Although several methods for creating bioglass–polymer composites exist, they require dissolution of the polymer, controlled phase separation, and appear to have an upper limit of ∼30 vol.% bioglass. Cold sintering is a novel technique for the densification of ceramics and glasses which utilizes a liquid phase and pressure to allow the production of components at reduced temperatures. We demonstrate that cold sintering (100°C) of Bioglass 45S5 powder produced via flame spray pyrolysis and the fabrication of Bioglass 45S5–polymer composites. Assessment of the in vitro response revealed that composites were not cytotoxic. Solid-state 31P and 29Si MAS NMR studies of the silicon and phosphorus speciation in the glass powder, as-received, wetted, and sintered samples show similarities to reactions expected when bioglass is implanted in the body which along with Raman spectroscopy data gave insight into the cold sintering densification mechanism.